America – China Trade War on Triangle Currency Shock - Hs, Arisyahidin (Prosiding Seminar, 2020)
This paper is to analyze the impact of trade war United States – Republic of China on ASEAN currency shock with the subject are the triangle counties; Indonesia, Malaysia, and Singapore. By comparing currency of those 3 states, we resulted the different impact of trade war of US–China on each country. Foreign exchange of Indonesia Rupiah is more volatile than Malaysia and Singapore. It mean that influence of US-China trading war on currency shock is depend on the economics power of each countries in the international trading. Indonesia as an emerging country also became the alternative penetration target. Besides the difference of international transaction system on those countries, we realize that Indonesia is a big country, so that the volume of consumptive is exactly large of amount.